Feasibility about Establishment of Hostel at Tourism Destination - Zhou, Yuan (Lapin ammattikorkeakoulu, 2017)
The purpose of this thesis is to explore and describe the needs and services offered by a hostel type accommodation in Finland Rovaniemi region. In the study, the author will point out comprehensive conceptions of measuring and proving the profitability and practicality of a start-up accommodation in Northern Finland. In addition, there is attempt to provide a general idea of starting business in Finland and to explore the processes of how to enter the accommodation sector. The theoretical background highlights the Finnish regulations and policies needed for small business in tourism and hospitality fields, government’s policy preferences concerning to tourism industry, processes of starting a business in Finland. The data collected for this thesis included an interview of a representative of hostel sector as well as survey material collected from potential target groups through the internet. The author used both quantitative and qualitative methods to analyse the material related to wishes, perspectives and suggestions on accommodation establishments. The qualitative approach comprises an interview to figure out the perspectives of Finnish tourism market and feasibility of this hostel business. And one open-ended question in the questionnaire. The aim of this research is to figure out the practical needs of potential customers and combine the results with analysis of competitors in Rovaniemi.